ANALISIS FAKTOR-FAKTOR MOTIVASIONAL PESERTA DIDIK SMA DALAM MENGIKUTI BIMBINGAN BELAJAR DI LUAR SEKOLAH - Nur Amaliyah Hanum; Djum Djum Noor Benty; Ahmad Yusuf Sobri (Universitas Negeri Malang, 2018)
Abstract: The Analysis of Motivational Factors of High School Students in Attending Course Institutions at Malang City. The purpose of this research is to find new factors, to know the contribution level of each factor, and to find the most dominant factor of high school students in attending course institutions at Malang City. This research uses quantitative approach with descriptive exploratory research design. The research found that there were 9 new factors that is: (a) assessment factor, (b) recognition factor, (c) punishment factor, (d) ability factor, (e) success factor, (f) ridicule factor, (g) social needs factor, (h) appreciation factor, and (i) competition factor. Keywords: motivation of high school students, attending course institutions at Malang CityAbstrak: Tujuan penelitian ini untuk menemukan faktor-faktor baru, mengetahui tingkat kontribusi masing-masing faktor, dan menemukan faktor yang paling dominan pada peserta didik SMA dalam mengikuti bimbingan belajar di luar sekolah Se-Kota Malang. Penelitian ini menggunakan pendekatan kuantitatif dengan rancangan penelitian bersifat deskriptif eksploratori. Hasil penelitian menemukan bahwa terdapat 9 faktor baru yaitu: (a) faktor penilaian, (b) faktor pengakuan, (c) faktor hukuman, (d) faktor kemampuan, (e) faktor keberhasilan, (f) faktor ejekan, (g) faktor kebutuhan sosial, (h) faktor penghargaan, dan (i) faktor persaingan. Kata kunci: motivasi peserta didik SMA, mengikuti bimbingan belajar di luar sekolah